PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD DAN PENGARUHNYA TERHADAP HASIL BELAJAR KOGNITIF DAN KECAKAPAN SOSIAL DITINJAU DARI SIKAP ILMIAH PESERTA DIDIK - Hadi Kusuma Ningrat (Universitas Islam Negeri (UIN) Mataram, 2018)
This study aims to determine the effect of STAD type cooperative learning model that is integrated through a scientific attitude toward the students' cognitive learning outcomes and social skills. The research method used is a quasi-experimental method with 2x2 factorial research design. The population of the study was students SMPN 1 Sakra Lombok Timur NTB. The sample is 64 students, divided into two classes. The research instrument is in the form of a questionnaire of social skills, a questionnaire of scientific attitudes, and tests of cognitive learning outcomes given at the beginning and end of the study. The data of the research were analyzed with Anakova two lanes. The results showed that (1) the students who used STAD type cooperative learning model differed significantly on the cognitive learning outcomes compared to the students who studied with direct learning, (2) the students who had high scientific attitude were not significantly different in the cognitive learning outcomes compared to the students with (3) there is no interaction effect between the learning model and the scientific attitude toward the students' cognitive learning outcomes, (4) the students who learn to use STAD type cooperative learning model differ significantly on social skills aspect than the students who learn by direct learning, 5) students who have a high scientific attitude are not significantly different in the aspects of social skills than students with low scientific attitude, (6) there is interaction influence between the learning model with the scientific attitude toward students' social skills.